2008
DOI: 10.1074/jbc.c700171200
|View full text |Cite
|
Sign up to set email alerts
|

Epac, in Synergy with cAMP-dependent Protein Kinase (PKA), Is Required for cAMP-mediated Mitogenesis

Abstract: cAMP stimulates proliferation in many cell types. For many years, cAMP-dependent protein kinase (PKA) represented the only known cAMP effector. PKA, however, does not fully mimic the action of cAMP, indicating the existence of a PKA-independent component. Since cAMP-mediated activation of the G-protein Rap1 and its phosphorylation by PKA are strictly required for the effects of cAMP on mitogenesis, we hypothesized that the Rap1 activator Epac might represent the PKAindependent factor. Here we report that Epac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 37 publications
4
85
0
Order By: Relevance
“…We have recently reported that, in the PCCL3 thyroid cell line, both PKA and Epac are synergistically involved in thyroidstimulating hormone (TSH) action (11). Closer examination of the kinetic profile of Rap1 activation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported that, in the PCCL3 thyroid cell line, both PKA and Epac are synergistically involved in thyroidstimulating hormone (TSH) action (11). Closer examination of the kinetic profile of Rap1 activation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3, the PKA-specific analog N 6 -benzoylcAMP activated Rap1 with kinetics consistent with the sustained phase described above. We then turned to a genetic approach, exploiting the observation that cAMP is not able to activate Rap1 in human embryonic kidney cells unless Epac is expressed (11). This model provides us the opportunity to express constitutively active forms of Epac and PKA and to assess their ability to activate Rap1 in the absence of cAMP.…”
Section: Volume 284 • Number 40 • October 2 2009mentioning
confidence: 99%
See 1 more Smart Citation
“…Activated Rap1 can bind to RAPL, a Rap1 binding molecule, and promote cell polarization by activating integrins [36]. PKA may also directly activate and regulate Epac1 and Rap1 [36] [37]. Interestingly, TGF-beta inhibits Epac1 expression via a Smad3-dependent process [36].…”
Section: The Role Of Adenosine and Its Receptors In Granulation Tissumentioning
confidence: 99%
“…This pathway integrates extracellular stimuli through the phosphorylation of c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase (ERK), p38, and other kinases (Kyosseva, 2004b;Kyosseva et al, 1999;Sweatt, 2001). Similar to the MAPK-associated pathway, 3 0 -5 0 -cyclic adenosine monophosphate (cAMP)-associated pathways are also coupled to activation of neurotransmitter receptors, and modulate cellular functions through the activation of protein kinase A (PKA), exchange protein activated by cAMP (EPAC), and other molecules (Borland et al, 2009;Cheng et al, 2008;Hochbaum et al, 2008;Ma et al, 2009;Roberson et al, 1999;Sands and Palmer, 2008). Alterations of the MAPK-and cAMP-associated signaling pathways may impact intracellular Ca + + levels, neurotransmitter receptors, transcription factors, crosstalk between signaling pathways, and other biological functions critical for neuroplasticity (Gelinas et al, 2008;Reichenberg, 2010;Sands and Palmer, 2008).…”
Section: Introductionmentioning
confidence: 99%